Individual Motivations and Network Effects: A Multilevel Analysis of the Structure of Online Social Relationships. Issue 1 (May 2015) - Welles, Brooke Foucault; Contractor, Noshir
This article explores the relative influence of individual and network-level effects on the emergence of online social relationships. Using network modeling and data drawn from logs of social behavior inside the virtual world Second Life, we combine individual- and network-level theories into an integrated model of online social relationship formation. Results reveal that time spent online and the network pressure toward balance (individuals tending to form relationships with others who have relationships in common) predict the emergence of online relationship ties, while gender, age, proximity, homophily (the tendency of individuals to form relationships among people with similar traits), and preferential attachment are not significant predictors within the observed networks. We discuss these results in light of existing research on online social relationships and describe how digital data and network analytics enable novel insights about the emergence of online social relationships.